Fatores de manutenção e regressão da língua e cultura alemãs no município de Missal - Paraná. - Rosa, Eliane Kreutz (2011)
The present work has as its theme the study of the German language and culture in Missal, a municipality located in the extreme west of the state of Paraná, which provides an expressive context of languages and cultures in contact, some resulting from the situation of border among Brazil, Paraguay and Argentina, a place called Tríplice Fronteira, others are a result of a migration process. Taking this context into account, we wonder why and what factors lead the residents of Missal, two hundred years after their immigration, to speak German (in its dialectal variety Hunsrückisch/ Brasildeutsch) and express, through parties and other local traditions, their linguistic and cultural identity. Bearing these questions in mind, the aim of this research is to analyze the factors that underlie the maintenance and regression of the German language and culture in this municipality. Although we acknowledge that language is part of individuals own culture and social group, both language and culture will be analyzed separately, i.e, the influence of cultural aspects regarding the maintenance and regression of the German language and culture. With this study, we intend to contribute to other previous studies, especially in the western region of Paraná, about bilingualism, identity and minority languages in complex sociolinguistic contexts in relation to bi(multi)lingualism from authors such as Pereira (1999); Heye (2003); Damke (1988, 1992, 1997, 1998, 2005, 2006, 2008); Savedra (2003, 2009); von Borstel (1992, 1999, 2011).This study also aims to contribute to the appreciation and maintenance of the German language and culture, not only in Missal, but also in other localities where bilingualism occurs. In this sense, this work is relevant to both current speakers and future generations, German descendants or not. This qualitative ethnographic research will be based on a Sociolinguistic perspective, focusing on concepts of identity, bilingualism, language/culture and linguistic policies. It is understood that the construction of a more critical human being, more responsive to other people´s culture, is only possible through the acceptance of difference and, in this sense, accepting an identity that is different from yours is a sign of respect, without stigmatizing culture and beliefs, especially the language, since languages exist because of speakers and their history is unquestionably linked (CALVET, 2002). Based on Calvet (2002), Napolitano (2005) e Damke (2008) attitudes of unity in diversity, of respect and of a pacific coexistence in this linguistic, cultural and ethnical mosaic which constitute Brazil is possible, acceptable, normal.